Next-generation counseling virtual reality as a transformative tool for immersive psychological therapy - alzet Rama; Wiki Lofandri; anggi Firmanjaya Saputra (Indonesian Counselor Association (IKI), 2024)
The rapid evolution of immersive technologies has created new opportunities for innovation in psychological counseling. This article investigates Virtual Reality (VR) as a transformative tool for next-generation counseling, emphasizing its potential to deliver immersive psychological therapy tailored to digital natives. Unlike conventional face-to-face approaches, VR enables controlled, interactive, and safe therapeutic environments that enhance emotional presence, reduce stigma, and improve treatment adherence. Recent studies (2021–2025) highlight VR’s effectiveness in addressing anxiety, phobias, post-traumatic stress, and stress regulation, while also demonstrating its promise for preventive and educational mental health practices. This study employs a systematic literature review supported by pilot case observations to assess the effectiveness and limitations of VR-based counseling. Findings reveal that immersive VR experiences can strengthen client–counselor engagement, foster motivation, and personalize therapeutic pathways through adaptive scenarios and real-time feedback. Moreover, the integration of VR aligns with the vision of Society 5.0, in which human-centered technology addresses complex psychological and social challenges. The study contributes to the growing discourse on digital mental health by positioning VR not merely as a supplementary medium but as a paradigm shift in counseling practice. Future research directions include the development of scalable VR platforms for clinical, educational, and community-based interventions, alongside critical considerations of accessibility, ethics, and long-term psychological outcomes